Alarm anti‐protease trappin‐2 negatively correlates with proinflammatory cytokines in patients with periodontitis. Issue 1 (6th February 2018) - Afacan, Beral; Öztürk, Veli Özgen; Emingil, Gülnur; Köse, Timur; Bostanci, Nagihan
Abstract: Background: Trappin‐2 is a potent biologically active serine protease inhibitor with anti‐inflammatory properties that has also been characterized as an "alarm anti‐protease." Although the importance of trappin‐2 in several chronic infections has been demonstrated, its potential involvement in periodontitis remains undefined. This study aims to investigate salivary levels of trappin‐2 and interleukin (IL)‐1β in periodontally healthy individuals and patients with gingivitis or generalized chronic periodontitis (CP) or aggressive periodontitis (GAgP). Methods: Whole unstimulated saliva samples were collected from 80 systemically healthy and non‐smoking individuals before full‐mouth periodontal examination. Trappin‐2 and IL‐1β were analyzed by enzyme‐linked immunosorbent assay and reported as nanograms per milligram after calibration for total protein levels. Results: Correlation analysis revealed negative association between trappin‐2 and IL‐1β levels. Trappin‐2 also showed strong negative correlation with clinical periodontal parameters, in contrast to IL‐1β, which showed positive correlation. Trappin‐2 levels were significantly lower in individuals with CP and GAgP, but not gingivitis, compared with healthy individuals. Reduced salivary concentrations of trappin‐2 had high sensitivity and specificity to distinguish health from periodontitis. Conclusions: Trappin‐2 is abundant in the saliva of individuals with healthy periodontium in line with its role as an "anti‐alarm" protease. Decreased salivary trappin‐2 and increased IL‐1β levels in individuals with periodontitis, compared with healthy individuals, may implicate a potential antiprotease/proinflammatory cytokine imbalance, resulting in impaired host protective capacity.